THE EU-28 MILK SECTOR TRENDS IN THE PERIOD 2009-2018 - Agatha POPESCU; Elena STOIAN; Valentin ȘERBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the EU-28 oil seeds sector in terms of cultivated area, production and yield for rape and turnip rape, sunflower and soybean, based on the data provided by Eurostat for the period 2008-2018. Growth rate, index method, descriptive statistics, correlations and regression equations were used to identify the trends and connections between these indicators. In 2018, the EU-28 cultivated 11.8 million ha with oil seeds crops, of which 58% rape, 33.8% sunflower and 8 % soybean. Seeds production reached 35 million tonnes, being by 30 % higher than in 2008. The average yield accounted for 3.2 t/ha in case of rape, 2.4 t/ha sunflower and 2.8 t/ha soybean seeds. The main producers of rape seeds are France, Germany, Poland, United Kingdom and Romania, and in case of sunflower are Romania, Bulgaria, Italy and France. The correlations and regression models indicated that for increasing production, yield improvement of sunflower and rape and also cultivated surface of soybean to increase. The lack of incentives for oil seeds producers in the EU and the higher payments for protein crops in order to balance the protein deficit on the EU market and reduce imports, will affect oilseeds for sure producers and production. As a result, it is expected as soybean to be cultivated on larger surfaces and sunflower cultivated area to decline.